2020
DOI: 10.1177/0361198120915886
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Willingness to Pool in Ride-Hailing Trips

Abstract: In the past decade, transportation network companies (TNCs) such as Uber, Lyft, and Via have established themselves as a viable transportation alternative to other modes. However, the popularity of these services has come with a fair share of criticism for their negative externalities such as increasing vehicle miles traveled and congestion in cities. Pooled ride-hailing trips, in which all or a part of two individual (or group) trips are combined in and served by a single vehicle, have the potential to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…The majority of the respondents in the sample were students, who already have discounted seasonal tickets for local transportation in the city, explaining why PV is not relevant to them for short and occasional trips. Most recently, Hou et al (31) investigated the willingness to pool in ridehailing trips. They found that the willingness to share rides is primarily a time-cost tradeoff.…”
Section: Discussion Recommendations and Implications For Academicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the respondents in the sample were students, who already have discounted seasonal tickets for local transportation in the city, explaining why PV is not relevant to them for short and occasional trips. Most recently, Hou et al (31) investigated the willingness to pool in ridehailing trips. They found that the willingness to share rides is primarily a time-cost tradeoff.…”
Section: Discussion Recommendations and Implications For Academicsmentioning
confidence: 99%
“…The study of Lavieri and Bhat (30) set another focus and examined willingness to share and investigated the adoption of shared rides. Hou et al (31) investigated the willingness to pool in ridehailing trips with linear regression and machine-learning models. They found that the willingness to share rides is at first a time-cost tradeoff.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Leveraging the same Chicago dataset used in our study, Hou et al and Xu et al took a similar approach to study the ratio of shared trips to total trips between O-D pairs (binned by pickup and drop-off census tracts) as a regression-based ML problem (Hou et al, 2020;Xu et al, 2021). They found that that socio-demographic variables as well as pickup/drop-off in airport census tracts have the highest predictive power, but both reported relatively large unexplained variance and high sensitivity to outlier observations.…”
Section: Factors Associated With Willingness To Sharementioning
confidence: 99%
“…The publicly available ride-hailing data from the City of Chicago has provided an unpreceded opportunity for empirical understanding of ridehailing demand patterns (Ghaffar et al, 2020;Yan et al, 2020), relationship with transit services (Barajas and Brown, 2021), and neighborhood characteristics (Marquet, 2020). Since it has a unique feature of observing which trips were requested to be shared, recent studies with this data attempted to understand the determinants of WTS (Dean and Kockelman, 2021;Hou et al, 2020;Tu et al, 2021;Xu et al, 2021). The results of these studies reveal key factors affecting WTS, but only focusing on the aggregate level between origin-destination (O-D) pairs of census tracts.…”
Section: Introductionmentioning
confidence: 99%
“…Ridesplitting is a ridesourcing service that involves volunteering to share a ridesourcing ride with someone at a reduced cost, and the driver in a ridesplitting service is for-hire (instead of a traveler) (21). The current literature on ridesplitting mainly focuses on the following three distinctive directions: (a) analyzing the characteristics of ridesplitting through the method of comparison (20,21); (b) exploring the choice behavior and willingness of adopting ridesplitting (22)(23)(24)(25); and (c) discussing the potentiality of ridesplitting (26,27).…”
Section: Studies Of Ridesplitting Based On Observed Datamentioning
confidence: 99%